Prevalence of Dental Fluorosis among Southern Jordanian Population - Amjad M. Al Warawreh; Zaid H. Al Tamimi; Mohammad I. Al Qatawna; Aseel A. Al Momani; Mohammed R. Al Mhaidat; Waddah S. El Naji; Salem AlSaraireh (Hindawi Limited, 2020)
Introduction. Jordan is one of the Middle Eastern countries that is classified as a poor water resource country. People in Jordan consume any available water. In the south of Jordan, water resources are limited. The drinking water contains high levels of fluoride, which in turn leads to augmented danger of both skeletal and dental fluorosis. Aims. This study is focused on evaluating the pervasiveness of dental fluorosis among patients of Karak City and assessing the degree and distribution of fluorosis. Materials and Methods. This research focuses on 2,512 patients ranging from 12 to 52 years old seeking dental treatment in the Dental Department at "Prince Ali ben Al Houssin Hospital" in Karak City. Dental fluorosis status was assessed by using Modified Dean's Fluorosis Index." The data collected were subjected to statistical analysis. Results. The dental fluorosis prevalence within our sample was 39.9% in Karak City. Females were more influenced than males, and fluorosis was detected more often in those who drank tap water and was more common in a very mild and localized form. Conclusion. Fluorosis necessitates constant observation, and future study in terms of the intake in Jordan is recommended in terms of all sources. It would not be too soon to note that the supply of drinking water needs to be changed in South Jordan.